"Eu sou velha?": um estudo sobre significados atribuídos à velhice, junto a mulheres que participam do Trabalho Social com Idosos no SESC – MA, em São Luís - FELIPE, Thayza Wanessa Silva Souza (2015)
This study aims to identify the meanings attributed to old age based on interviews with elderly participants of Social Work with Elderly (TSI), developed by SESC Deodoro, in São Luís - MA. Focusing on understanding the different ways that these elderly live this phase of life, their experiences were linked to social markers that make possible such distinction. Considering the categories used for specific age groups presuppose the recognition of universal principles between individuals of the same age, in the case of the elderly, they are not taken into account to define differences and peculiarities related to social class, issues of gender, race, religion, among others, that may exist in the group. Moreover, in the current context, the active aging image has prevailed as a ready-made model correct lifestyle to this stage of life. Due the spread of this image, produced and supported by different specialists, that many older people are organizing themselves in groups and programs for seniors that have a set of speeches focused on body maintenance techniques, healthy food, walks, dances, and other forms of leisure that show how those who do not feel old should behave. The empirical research was constituted with ten women, aged from 60 years Who participate assiduously in any activity offered by TSI. Through individual and focus interviews, without pre-defined script, these womens were allowed to tell parts from their life stories, in their way of think, behave, their worldviews, conceptions of old age experience, about their bodies, different relationships in which are embedded with family, friends, peer group, speechs that allowed knowing some of the meanings attributed by these people to be old. For the interviewees, the meaning of the current phase in which they live is perceived as their statements, as a stage of achievements that could not be experienced by them, when younger. It is a moment of pleasure, independence, freedom, which is configured in a stage of life they are living for themselves. So they show often a denial of old age, among them predominates the notion that being old is always the "other", the bad tempered, which does not take care, that lives indoors, not participating groups of coexistence, going against the lifestyle they have. In addition, using the memory of older also provided understand the formation processes of different subjects, indicating the complexity of understanding of aging. Differents socials markers such as class, gender, education, race and religion intersect the experience of established subjects as elderly, which directly influences the way one lives his old age, but also the meanings that associate with that stage of life. Thus, the aging analysis should not be close to the issues of biological, because old age while built category is related to different social aspects.